Molecular basis for antioxidant enzymes in mediating copper detoxification in the nematode Caenorhabditis elegans. - Shaojuan Song (Public Library of Science (PLoS), 2014)
Antioxidant enzymes play a major role in defending against oxidative damage by copper. However, few studies have been performed to determine which antioxidant enzymes respond to and are necessary for copper detoxification. In this study, we examined both the activities and mRNA levels of SOD, CAT, and GPX under excessive copper stress in Caenorhabditis elegans, which is a powerful model for toxicity studies. Then, taking advantage of the genetics of this model, we assessed the lethal concentration (LC50) values of copper for related mutant strains. The results showed that the SOD, CAT, and GPX activities were significantly greater in treated groups than in controls. The mRNA levels of sod-3, sod-5, ctl-1, ctl-2, and almost all gpx genes were also significantly greater in treated groups than in controls. Among tested mutants, the sod-5, ctl-1, gpx-3, gpx-4, and gpx-6 variants exhibited hypersensitivity to copper. The strains with SOD or CAT over expression were reduced sensitive to copper. Mutations in daf-2 and age-1, which are involved in the insulin/insulin-like growth factor-1 signaling pathway, result in reduced sensitivity to stress. Here, we showed that LC50 values for copper in daf-2 and age-1 mutants were significantly greater than in N2 worms. However, the LC50 values in daf-16;daf-2 and daf-16;age-1 mutants were significantly reduced than in daf-2 and age-1 mutants, implying that reduced copper sensitivity is influenced by DAF-16-related functioning. SOD, CAT, and GPX activities and the mRNA levels of the associated copper responsive genes were significantly increased in daf-2 and age-1 mutants compared to N2. Additionally, the activities of SOD, CAT, and GPX were greater in these mutants than in N2 when treated with copper. Our results not only support the theory that antioxidant enzymes play an important role in copper detoxification but also identify the response and the genes involved in these processes.